Escape manoeuvres in the spiny dogfish (Squalus acanthias) - Domenici, Paolo; Standen, Emily M.; Levine, Robert P. (Journal of Experimental Biology, 2004)
The locomotor performance of dogfish during escape responses was observed by means of high-speed video. Dogfish show C-type escape responses that are comparable with those shown previously in teleosts. Dogfish show high variability of turning rates of the anterior part of the body (head to centre of mass), i.e. with peak values from 434 to 1023 deg. s-1. We suggest that this variability may be due to the presence of two types of escape manoeuvres, i.e. responses with high and low turning rates, as previously found in a teleost species. Fast responses (i.e. with high maximum turning rates, ranging between 766 and 1023 deg. s-1) showed significantly higher locomotor performance than slow responses (i.e. with low maximum turning rates, ranging between 434 and 593 deg. s-1) in terms of distance covered, speed and acceleration, although no differences were found in the turning radius of the centre of mass during the escape manoeuvres. The existence of two types of escape responses would have implications in terms of both neural control and muscular activation patterns. When compared with literature data for the locomotor performance of bony fishes, dogfish showed relatively low speed and acceleration, comparable turning rates and a turning radius that is in the low part of the range when compared with teleosts, indicating relatively high manoeuvrability. The locomotor performance observed in dogfish is consistent with their morphological characteristics: (1) low locomotor performance associated with low thrust developed by their relatively small posterior depth of section and (2) relatively high manoeuvrability associated with their high flexibility.